In vitro study of white spot lesion: Maxilla and mandibular teeth - Alizae Marny Mohamed; Kiong Hung Wong; Wan Jen Lee; Murshida Marizan Nor; Haizal Mohd Hussaini; Tanti Irawati Rosli (Elsevier, 2018)
Aim: The aim of the study was to evaluate the effect of resin infiltration on colour changes and surface roughness of artificial white spot lesions (WSLs) on maxillary and mandibular premolar. Materials and methods: Sixty (60) extracted sound Maxilla (Mx) and Mandibular (Mn) premolars were randomly divided into 2 groups (test and control). Artificial WSLs were produced on buccal surface of teeth and were immersed in artificial saliva for 8 weeks. Colour components (L∗, a∗, b∗) and surface roughness (Sa∗) were assessed on 40 teeth using colour difference meter RD-100 and Alicona® Infinite Focus profilometer respectively. The measurements were done at baseline (T1), directly after artificial WSLs (T2), after 24 hours immersed in saliva and application of resin (T3) and immersion in artificial saliva for 1 (T4), 2 (T5), 4 (T6), 6 (T7) and 8 (T8) weeks. SEM images analysis were carried out on 20 teeth in four time points. Results: The values of L∗ (lightness), b∗ (yellow/blue) and Sa∗ (surface roughness) are gradually reduced to the baseline value. Whereas, the value of a∗ gradually increased with distinct treatment time to achieve the baseline value. The higher value of L∗ and Sa∗, the whiter the lesion suggesting higher degree of enamel demineralization and surface roughness. Lower L∗ values suggest a masking colour effect. Conclusion: The material produced favorable esthetics on colour and the surface roughness of teeth at distinct treatment times. It is recommended to be used to improve WSL post orthodontic treatment. Keywords: Esthetics, Infiltrant, Surface roughness, White spot lesion